BINGE EATING DISORDER AND QUALITY OF LIFE OF CANDIDATES TO BARIATRIC SURGERY - COSTA,Ana Júlia Rosa Barcelos (2015)
Background : Obesity decreases the quality of life, which is aggravated by the association of comorbidities, and the binge eating disorder is directly related to body image and predisposes to overweight. Aim: Evaluate association between the presence and the level of binge eating disorder and the quality of life of the obese candidates for bariatric surgery. Methods : Cross-sectional study analyzing anthropometric data (weight and height) and socioeconomics (age, sex, marital status, education and income). The application of Binge Eating Scale was held for diagnosis of Binge Eating Disorder and the Medical Outcomes Study 36-item Short-From Health Survey to assess the quality of life. Results : Total sample studied was 96 patients, mean age 38.15±9.6 years, 80.2% female, 67.7% married, 41% with complete and incomplete higher education, 77.1% with lower income or equal to four the minimum salary, 59.3% with grade III obesity. Binge eating disorder was observed in 44.2% of patients (29.9% moderate and 14.3% severe), and these had the worst scores in all domains of quality of life SF36 scale; however, this difference was not statistically significant. Only the nutritional status presented significant statistically association with the presence of binge eating disorder. Conclusion : High prevalence of patients with binge eating disorder was found and they presented the worst scores in all domains of quality of life.